(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction : HbD Punjab is also known as HbD Los Angeles was first described by Itano in 1951. In HbD point mutation in beta globin chain occurs . HbD associated with HbS in which one gene carries HbD while other gene carries HbS mutation . Infants are at increased risk of life threatening complications like severe anaemia , splenic sequestration , overwhelming septicaemia . Method: Two siblings one 9 year old male and other 4 year old male patients were presented with covid 19 infection in the hospital . Both were known case of sickle cell disease . There blood samples were taken and cbc , retic and HPLC was done . Both were diagnosed as HbSD Heterozygosity by HPLC method .Their mother was a know case of sickle cell trait and father was known case of HbD Punjab trait. RESULT : In above study diagnosis of HbSD in both siblings was confirmed by HPLC. Since both their parents were carriers of sickle cell trait(mother) and HbD trait(father) . HbSD is a heterozygous state beta 121 glutamine residues stabilise the polymer and increases intracellular polymerization of HbS and increase sickling phenomenon . CONCLUSION : HbSD is a rare but very serious disorder with high prevalence in northern part of India . It is a genetically inherited disorder occurs when either of one parent is HbD trait and other one being HbS trait.